Regional Weak and Strong Stabilization of Semilinear Systems with Decay Estimate - Alami, A. El; Boutoulout, A. (Discontinuity, Nonlinearity, and Complexity, 2026)
The aim of this paper is to develop the question of the regional stabilization for infinite-semilinear parabolic systems on a spatial domain Ω. precisely the study of such system on a subregion ω of Ω. We consider a decomposition of the state space via the spectral properties of the system. Then we apply this approach to regional strong and weak stabilization problem using bounded feedback. Some applications and simulations are presented.